1991
DOI: 10.1128/iai.59.3.1002-1007.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 15-kilodalton surface glycoprotein on sporozoites of Cryptosporidium parvum

Abstract: An immunoglobulin A monoclonal antibody (MAb5C3) was developed against a 15-kDa surface glycoprotein (GP15) of Cryptosporidium parvum sporozoites. Indirect immunofluorescence and colloidal gold immunoelectron microscopy revealed that the antibody reacted with both the sporozoite and merozoite surface plasma membranes. On Western immunoblots, MAb5C3 binding was found to be strongly inhibited when 200 mM N-acetylglucosamine was used as a competing sugar. N-Acetylgalactosamine inhibited binding of the antibody on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…Six C. parvum sporozoite proteins have been cloned so far. Five were localised to either the sporozoite surface, CP15/60 [62,63], CP15 [64] and P23 [65,66], or to the micronemes, the thrombospondin-related adhesive protein of Cryptosporidium-1 (TRAP-C1) [67] and GP900 [68], while the precise location of the sporozoite cysteine-rich protein (SCRP) (Spano et al, unpublished) is presently under study. CP15/60, CP15 and P23 are low mol.…”
Section: Surface and Micronemal Proteins Of Sporozoitesmentioning
confidence: 99%
See 3 more Smart Citations
“…Six C. parvum sporozoite proteins have been cloned so far. Five were localised to either the sporozoite surface, CP15/60 [62,63], CP15 [64] and P23 [65,66], or to the micronemes, the thrombospondin-related adhesive protein of Cryptosporidium-1 (TRAP-C1) [67] and GP900 [68], while the precise location of the sporozoite cysteine-rich protein (SCRP) (Spano et al, unpublished) is presently under study. CP15/60, CP15 and P23 are low mol.…”
Section: Surface and Micronemal Proteins Of Sporozoitesmentioning
confidence: 99%
“…polypeptides of 148, 119 and 111 aa, respectively, whose genes were cloned by screening C. parvum expression libraries with mAb or polyclonal antibodies raised against oocyst/sporozoite lysates [63,64,66,69]. Despite the lack of a putative leader peptide for extracellular targeting and of transmembrane or GPI-anchoring signals in the aa sequence of CP15/60, CP15 and P23, immuno¯uorescence analyses suggested that these three proteins are located on the membrane of sporozoites, and in the case of CP15/60 and P23 on the membrane of merozoites [62,65]. Subcellular fractionation shows that P23 can be found in the micronemes of C. parvum sporozoites (Petry et al, unpublished).…”
Section: Surface and Micronemal Proteins Of Sporozoitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified a 15 kDa surface glycoprotein on sporozoites of C. paruum, which was thought to be sloughed from the surface of sporozoites during gliding [4]. mAbs were recently made to this and other parasite molecules in our laboratory [5], some of which were employed to determine whether CP15 may be a second antigen involved in sporozoite substrate attachment.…”
Section: Introductionmentioning
confidence: 99%